Peran Kepemimpinan Dalam Memotivasi Dan Meningkatkan Kinerja Karyawan PT. Pulau Sambu Desa Kuala Enok Kecamatan Tanah Merah Kabupaten Indragiri Hilir - Putri Wilhelmina; Efni Anita; Rabiyatul Alawiyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Leadership is a science that comprehensively examines how to direct, influence and supervise others to carry out tasks in accordance with planned orders. motivation is a process of trying to influence someone to do something he wants. According to Amstron and Baron, performance is the result of work that has a strong relationship to the organization's strategic goals, customer satisfaction and makes an economic contribution. This research focuses on